MADRASAH CURRICULUM PLANNING IBTIDAIYAH PRIVATE UMMMUL QURAA - Amiruddin Siahaan; Abdul Rahim; Demu Wira Berutu; Desi Damayani Pohan; Zamzami Zamzami (Jurnal Sabilarrasyad, 2020)
The curriculum is one component that has an important role in the education system, because the curriculum is not only formulated about the objectives that must be achieved so as to clarify the direction of education, but also must provide an understanding of the learning experiences that each child must have. This type of research is field research, namely the type of research conducted intensively, in detail, and in depth on certain objects, namely qualitative research. The location of the study was at MIS UMMUL QURAA with informants from the Principal, Vice Principal for Curriculum, teachers and students. The results showed that: 1) curriculum management at MIS UMMUL QURAA began with planning and then the implementation of which has been running well, using the 2013 curriculum combined with local wisdom and provision of life skills; 2) supporting factors come from external and internal; 3) inhibiting factors are still found learning tools that are less professional and the habits of some educators who have not varied and passive; 4) curriculum management strategy starts from curriculum development by taking into account the conditions and needs of students according to the characteristics of the education unit, and 5) its implementation has an impact on the creation of better education, more adequate for students, increasing the performance of the teaching staff / staff, realization of understanding the community towards the importance of education, management of better quality educational resources and teaching staff, more perfect curriculum development, encouragement for educators to continue to innovate and meet the needs of education fundin